EPEN-10. 5-FU ENHANCES RADIATION THERAPY IN IN VITRO AND IN VIVO TREATMENT OF 1q+ PFA EPENDYMOMA. (23rd April 2019) - Griesinger, Andrea; Donson, Andrew; Amani, Vladimir; Domman, Andrew; Pierce, Angela; Court, Benjamin Van; Karam, Sana; Steiner, Jenna; Serkova, Natalie; Dorris, Kathleen; Foreman, Nicholas
Abstract: BACKGROUND: Chemotherapy trials in relapsed pediatric ependymoma trials have failed to show reproducible benefit. High-risk 1q+PFA ependymoma show have a particularly bad outcome, with radiation and surgery showing no benefit at relapse. Using two 1q+PFA1 cell lines, we identified several ependymoma specific FDA-approved oncology drugs, including fluorouracil (5-FU). The goal of our study was to determine the effect of combining 5-FU and radiation in in-vitro and in-vivo 1q+PFA models. METHODS: MAF-811 and MAF-928 cell lines along with our newly established orthotopic xenografts MAF-811_XC and MAF-928_XC were used to measure treatment effects. Cesium radiation was used to treat cell lines and focal radiation was delivered to mice using 2Gy for 5 days. 30mg/kg 5-FU was dosed in mice once prior to radiation, once during, and weekly following radiation treatment for a total of 6 rounds of 5-FU. RESULTS: In-vitro studies, treating both 1q+PFA1 cell lines with escalating doses of 5-FU and radiation, we found synergistic effect on tritiated thymidine incorporation 7 days post radiation treatment. This effect was independent on sequence of drug and radiation dosage. In-vivo studies are ongoing with combining 10Gy focal radiation with 5-FU in both 1q+PFA xenografts. Preliminary studies have shown combination treatment appears to be well tolerated with 5-FU dosing. CONCLUSION: 5-FU treatment enhances the effect of radiation therapy in 1q+PFA models. Furthermore, these studies are the first to use both in-vitro and in-vivo models as rationale for developing clinical trials for this high-risk patient populations. An upfront clinical trial in 1q+PFA patients has been purposed.